2020
DOI: 10.1088/2515-7639/ab60c4
|View full text |Cite
|
Sign up to set email alerts
|

Operational stability of perovskite light emitting diodes

Abstract: Organometal halide perovskite light emitting diodes (LEDs) have attracted a lot of attention in recent years, owing to the rapid progress in device efficiency. However, their short operational lifetime severely impedes the practical uses of these devices. The operating stability of perovskite LEDs are due to degradation due to ambient environment and degradation during operation. The former can be suppressed by encapsulation while the latter one is the intrinsic degradation due to the electrochemical stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 150 publications
(310 reference statements)
1
121
0
Order By: Relevance
“…[ 10,15–19 ] Although the sensitivity of the devices to atmospheric effects such as oxygen and water can be mitigated through effective packaging techniques, [ 20 ] there is also an intrinsic instability in the devices with the high electric fields experienced under LED operation. [ 21 ] This instability appears to be caused by a combination of ionic migration and Joule heating, [ 20,22–26 ] which ultimately leads to degradation of the device performance. In order to overcome these degradation processes, a comprehensive understanding of the degradation location in the device and underlying degradation mechanisms under device operation conditions is essential, thereby allowing a rational approach to stabilize operation.…”
Section: Figurementioning
confidence: 99%
“…[ 10,15–19 ] Although the sensitivity of the devices to atmospheric effects such as oxygen and water can be mitigated through effective packaging techniques, [ 20 ] there is also an intrinsic instability in the devices with the high electric fields experienced under LED operation. [ 21 ] This instability appears to be caused by a combination of ionic migration and Joule heating, [ 20,22–26 ] which ultimately leads to degradation of the device performance. In order to overcome these degradation processes, a comprehensive understanding of the degradation location in the device and underlying degradation mechanisms under device operation conditions is essential, thereby allowing a rational approach to stabilize operation.…”
Section: Figurementioning
confidence: 99%
“…[ 43 ] It may also slow down other intrinsic ionic migration effects, all of which play a major negative role in instability of perovskite LEDs, as summarized in recent review by So team, where the highest apparent reported luminance was 250 h at 100 cd m −2 . [ 129,130 ]…”
Section: Future Challengesmentioning
confidence: 99%
“…Beyond these limits, the operation lifetime of PeLEDs is far from the requirement for commercial use. [34]…”
Section: Status and Challengesmentioning
confidence: 99%